Factores de riesgo asociados a embarazo ectópico en pacientes del hospital Hipólito Unanue de Tacna, 2015-2020 - Hermoza Gutierrez, Catherine Guisel (2023)
Objective: To determine the risk factors associated with ectopic pregnancy in women treated at the Hipólito Unanue Hospital in Tacna during the years 2015 to 2020. Material and methods: Observational, retrospective study, the case-control in 181 patients with a definitive diagnosis. of ectopic pregnancy. Data were obtained from medical records. Data processing and analysis were carried out with SPSS Version 22 software. Absolute and relative frequencies and the Chi2 test were used. Results: The incidence of ectopic pregnancy was 0,87 % of all pregnancies. The risk factors that were associated were: maternal age of 20 to 29 years (p = 0,041), and history of cesarean section (p = 0,034). Women with ectopic pregnancy were characterized by having a maternal age of 20 to 29 years (47,5 %), secondary education level (63 %) and married marital status (36,5 %). Among gynecological-obstetric factors, nulliparity was present in 43,1 %, history of cesarean section 83,4%, history of abortion 42 %, history of ectopic pregnancy 9,9 %, history of STI 42 %, history of infertility 8,3 %, history of use of IUD 14,4 % and history of PID 16 %. The age of initiation of sexual relations was between 15 and 20 years 75.1 %, and a history of smoking 5,5 %. The clinical characteristics were: metrorrhagia and pelvic pain (49,7 %), followed by metrorrhagia, pelvic pain and adnexal mass (24,3 %). The location of the ectopic pregnancy was mostly tubal (86,7 %). Conclusion: The risk factors associated with ectopic pregnancy were adequate maternal age and history of cesarean section.